1988
DOI: 10.1113/jphysiol.1988.sp017199
|View full text |Cite
|
Sign up to set email alerts
|

Changes in binomial parameters of quantal release at crustacean motor axon terminals during presynaptic inhibition.

Abstract: SUMMARY1. The effects of presynaptic inhibition on quantal release of transmitter were investigated at neuromuscular junctions of the motor axon supplying one of the limb muscles of a crab (Pachygrapsus crassipes).2. Binomial analysis of transmitter release recorded at selected neuromuscular junctions with an extracellular 'macro-patch' electrode indicated high probability of release (p) from a limited number of available sites (n). During presynaptic inhibition, both n and p were reduced.3. The binomial model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 42 publications
3
12
1
Order By: Relevance
“…Presynaptic densities in L-neuron vesicle clouds vary considerably in length, with most extending through only one or two sections but others having lengths up to 1.5 m. At arthropod neuromuscular junctions most presynaptic densities extend into only one or two serial ultrathin (70 nm) sections (Atwood et al, 1993;Jia et al, 1993;Wojtowicz et al, 1994;King et al, 1996), although Atwood and Tse (1988) reported a pattern similar to the one we find for L-neurons at crayfish neuromuscular junctions. Similarly, presynaptic densities at output synapses made in a locust thoracic ganglion by motor neurons (Watson and Burrows, 1982) and an intersegmental interneuron (Watson and Burrows, 1983) can be longer than 1 m, although most are considerably shorter.…”
Section: Presynaptic Densities and Active Zonessupporting
confidence: 66%
“…Presynaptic densities in L-neuron vesicle clouds vary considerably in length, with most extending through only one or two sections but others having lengths up to 1.5 m. At arthropod neuromuscular junctions most presynaptic densities extend into only one or two serial ultrathin (70 nm) sections (Atwood et al, 1993;Jia et al, 1993;Wojtowicz et al, 1994;King et al, 1996), although Atwood and Tse (1988) reported a pattern similar to the one we find for L-neurons at crayfish neuromuscular junctions. Similarly, presynaptic densities at output synapses made in a locust thoracic ganglion by motor neurons (Watson and Burrows, 1982) and an intersegmental interneuron (Watson and Burrows, 1983) can be longer than 1 m, although most are considerably shorter.…”
Section: Presynaptic Densities and Active Zonessupporting
confidence: 66%
“…At both locations, the axoaxonal synapses are capable of effectively reducing the action potential or depolarization in the terminal Segev, 1990) and thus reducing the release of transmitter. Consequently, one or a few inhibitory axoaxonal synapses can reduce the effectiveness of many excitatory neuromuscular synapses (Atwood and Tse, 1988). The occurrence of axoaxonal synapses on branches of the excitatory axon itself (Fig.…”
Section: Location Of Axoaxonal Synapsesmentioning
confidence: 99%
“…In practice, physiological measurements have not often shown such an effect; only rarely has it been shown that impulse failure occurs in excitatory terminals during inhibition (Dudel, 1965). More frequently, there is reduction in amplitude of the excitatory action potential (Takeuchi and Takeuchi, 1966;Baxter and Bittner, 19811, but inhibition can occur even without this effect (Atwood and Tse, 1988). Thus, the off-shore axoaxonal synapses are not effective enough to block action potential propagation in most cases studied to date, but the possibility remains that at higher frequencies of stimulation, or over prolonged periods, such an effect could occur.…”
Section: Location Of Axoaxonal Synapsesmentioning
confidence: 99%
“…Scharstein 1979;Rospars and Lánský 1993;Bressloff 1995;Lánský and Rodriguez 1999a,b;Shimokawa et al 2000;Burkitt and Clark 2000;Feng and Brown 2000;Feng 2001;Pakdaman 2001). Details on the biophysics of excitable cell membranes, during primary afferent depolarisations and shunting inhibition in particular (Atwood et al 1984; Atwood and Tse 1988;Segev 1990;Graham and Redman 1994;Walmsley et al 1995;Lamotte d'Incamps et al 1998;Lamotte et al 1999;Cattaert et al 2001), are omitted.…”
Section: Introductionmentioning
confidence: 96%